Modelo de avaliação do potencial competitivo para instaladoras de sistemas fotovoltaicos - Rigo, Paula Donaduzzi (2022)
Electricity generation through photovoltaic technology is promising worldwide. In this market, photovoltaic systems’ installers are the link between the entire production chain and consumers. These companies are frequently the intermediary diffusers since they are responsible for disseminating the technology´s knowledge to the population through sales and systems installation. The number of active installers doubles every year in all regions of Brazil, reaching approximately 21,200 installers in 2022. Most of these companies are small, have few years of experience, and are adjusting their management and technical operations. Competitiveness among companies in this sector is enhanced by the nature of the photovoltaic systems integration service because, in the view of most investors, the solution that companies offer is the same. Consequently, installers need to studies that enhance their competitiveness, not only to continue meeting the growing demand for systems, but also to establish themselves as consolidated companies to gain market share against their competitors. This thesis proposes a model for evaluating the competitive potential for installers of photovoltaic systems. To develop the competitiveness performance measurement system, the Balanced Scorecard (BSC) model improved with Multi-Criteria Decision Aid (MCDA) methods were adopted. We selected 39 competitiveness factors in a systematic literature review, discussing and organizing them into BSC perspectives. Then, strategic objectives were developed for each factor and proposed Key Performance Indicators that measure them, allowing the selection by the installers according to their business model. The Content Validity Ratio method was applied with 51 managers of installing companies to select the strategic objectives considered essential for the company´s lasting competitiveness, reducing the BSC strategic map to 19 strategic objectives. The MCDA DEMATEL method was applied with experts in energy business management to build the map of cause-and-effect relationships and weight the BSC structure. Based on the final strategic map of the BSC, the mathematical formulation for the competitiveness performance measurement system was developed. Additive-type aggregation functions that consider cause-and-effect relationships and the weights of strategic objectives were built to reach a final competitiveness index. The professionalization, organization, and quality of delivery of the installers are essential for the timely development of photovoltaic energy in the country. Therefore, the analysis of competitive potential helps companies to reflect on their internal actions that increase or not the potential for growth in sales of systems, allowing these companies to carry out strategic monitoring, self-assessment of competitive performance, the establishment of goals, and establishment of initiatives to improve management and operations.